Reassessing the Focus of Medical Practice: From Diseases to Human Beings - Mezzich, Juan Enrique (2010)
Medical practice focused in human beings, taking into account both humanistic, and scientific aspects, as well as human rights is the main pathway to be followed by us, physicians; and this must lead us to always keep in mind that both medical art and science play for patients and not against them.